Adoption of knowledge management systems (KMS) in Universiti Teknologi Malaysia - Abubakari, Fatima (2017)
Knowledge Management System(KMS) has become progressively vital for teaching and learning, and also potentially become one of the most significant applications in Information Technology (IT). This study used a quantitative approach, seeking a causative explanation of the decision behaviour of individuals toward the acceptance of KMS in teaching and learning. Data was collected through a questionnaire from students and lecturers of Faculty of Education, Faculty of Science Faculty of Bioscience and Medical Engineering and Faculty of Mechanical Engineering in UTM. The study framework was based on the second version of the Technology Acceptance Model (TAM2) using eight factors from the framework, the factors are subjective norm, image, job relevant, output quality, result demonstrability, perceived ease of use, perceived usefulness and intention to use. The data were analysed using Structural Equation Modelling, in order to determine the factors that influence the adoption of KMS by lecturers and students in teaching and learning. Results shows that output quality is significantly determined by perceived usefulness and perceived ease of use, which are significantly determined by intention to use, perceived usefulness and subjective norm. But subjective norm is not significantly determined by perceived usefulness, result demonstrability, job relevant and image.